RESPONSE TO TREATMENT OF CHOROIDAL NEOVASCULARIZATION IN HIGHLY MYOPIC EYES WITH DOME-SHAPED MACULA: Two Years of Follow-Up. Issue 6 (June 2022) - Pozzo Giuffrida, Francesco; Leone, Gaia; Mainetti, Claudia; Galli, Davide; Dell'Arti, Laura; Mapelli, Chiara; Nassisi, Marco; Viola, Francesco
Abstract : Supplemental Digital Content is Available in the Text. The 2-year clinical outcomes of antivascular endothelial growth factor therapy in 54 eyes with myopic choroidal neovascularization were reported according to the presence of dome-shaped macula. Dome-shaped macula is not a significant negative prognostic factor in these patients; however, dome-shaped macula eyes are more prone to extrafoveal choroidal neovascularizations than non–dome-shaped macula eyes. Abstract : Purpose: To compare the 2-year outcome to antivascular endothelial growth factor therapy for myopic choroidal neovascularization (CNV) in the eyes with or without dome-shaped macula (DSM). Methods: Data from treatment-naive myopic CNV with a 2-year follow-up were retrospectively collected and divided into two groups according to the presence of DSM. The best-corrected visual acuity was acquired at baseline, 3, 12, and 24 months. The association between visual outcomes and CNV type and area, presence of scleral-derived feeder vessel, macular atrophy, and lacquer cracks at baseline was also evaluated. Results: Fifty-four eyes of 54 patients were included; 18 eyes (33.4%) had DSM. Choroidal neovascularization was foveal in 10 DSM eyes (55.6%) and in 30 non-DSM eyes (83.9%), P = 0.033. At baseline, the mean best-corrected visual acuity was significantly higher in the DSM group (68.33 ± 12.04 Early Treatment Diabetic Retinopathy Study letters, 20/40 Snellen) compared with the non-DSM group (57.75 ± 13.46 Early Treatment Diabetic Retinopathy Study letters, 20/72 Snellen; P = 0.007). This difference disappeared after 3 months and did not reoccur afterward. All other parameters were not significantly associated with visual outcomes. Conclusion: Overall, DSM does not represent a negative prognostic factor in response to antivascular endothelial growth factor therapy in myopic CNVs after 2 years. However, in DSM eyes, CNVs tend to be extrafoveal, thus ensuring a good visual prognosis from the earliest stage of the disease.